Diversity, dissent, and fragmentation in the #MeToo movement: the role of collective and individual dimensions - Bliuc, Ana-Maria; Hamilton, Tayla; Muntele, Daniela (Frontiers in Psychology, 2024)
Introduction In this research, we examine how intragroup fragmentation, which is the division of a group into smaller subgroups, interacts with different forms of action against gender inequality. We focused on two types of action: actions that promote social change and actions that encourage retribution. Methods We investigated these processes within the #MeToo social movement using data collected in Australia (N = 363) and Romania (N = 135). In both samples, we measured antecedents of ’group consciousness’ (previous experience with discrimination, empathic concern, and perspective taking) and its indicators (social identification, perceived group efficacy beliefs, and group emotions such as anger and contempt). As indicators of intragroup fragmentation, we measured endorsement of different categories of group behaviors such as pro-social change action versus pro-retribution action. To assess the predictive power of motivations for joining the movement (antecedents of group consciousness) and of group consciousness for either pro-social or retributive actions, we tested several structural equation models (SEMs). Results Our results indicate that the motivations for joining such social movements were more complex than anticipated, with perspective-taking emerging as a significant differentiator. Our analyses further show that different dimensions of group consciousness could predict support for either pro-social or retributive actions. Discussion These findings highlight the complexity of the intragroup processes in newly emerging, modern social movements such as #MeToo. Our findings have implications for the study of membership dynamics in social movements and suggest that strategies to mobilise support should be tailored to these complexities. Overall, this research contributes to the current understanding of intragroup dynamics in contemporary social movements, thereby providing insights that could inform both grassroots mobilisation strategies and policy interventions aiming to increase gender equality.